Strain-Induced Transformations of Bicyclo[3.1.0]hex-1-enes - Ghorai, Sourav; Lee, Daesung (Synthesis, 2021)
Bicyclo[3.1.0]hex-1-ene is a highly strained bicyclic intermediate that generates trimethylenemethane (TMM) diradical through breaking the C–C bond of its methylene cyclopropane moiety. The reactivity of bicyclo[3.1.0]hex-1-enes and trimethylenemethane (TMM) diradicals depend on the reaction temperature and substitution patterns. This short review covers various strain-induced transformations of bicyclo[3.1.0]hex-1-enes and their formal [3+2] cycloadditions through TMM diradicals and presents synthetic applications to natural products containing triquinane and tropone structures.1 Introduction2 Early Reports on Bicyclo[3.1.0]hex-1-enes3 Approaches to Form Bicyclo[3.1.0]hex-1-enes4 Structure and Reactivity of Bicyclo[3.1.0]hex-1-enes4.1 Isomerization4.2 Dimerization4.3 [3+2] Cycloaddition4.4 [4+2] Cycloaddition5 Synthetic Applications to Natural Products6 Summary and Outlook
Keywords: bicyclo[3.1.0]hex-1-enes; TMM diradical; dimerization; [3+2] cycloaddition; triquinanes